Question and Answers Forum

All Questions      Topic List

Limits Questions

Previous in All Question      Next in All Question      

Previous in Limits      Next in Limits      

Question Number 194891 by cortano12 last updated on 18/Jul/23

         lim_(x→3^+ )  ((((√x)−(√(x−3))−(√3))/( (√(x^2 −9)))) )=?

$$\:\:\:\:\:\:\:\:\:\underset{{x}\rightarrow\mathrm{3}^{+} } {\mathrm{lim}}\:\left(\frac{\sqrt{{x}}−\sqrt{{x}−\mathrm{3}}−\sqrt{\mathrm{3}}}{\:\sqrt{{x}^{\mathrm{2}} −\mathrm{9}}}\:\right)=? \\ $$

Answered by MM42 last updated on 18/Jul/23

lim_(x→3)  ((((√x)−(√3))/( (√(x−3))×(√(x+3)))) − ((√(x−3))/( (√(x−3))×(√(x+3)))) )  =lim_(x→3)  ((((√(x−3))×(√(x−3)))/( ((√x)+(√3))×(√(x−3))×(√(x+3)))) − ((√(x−3))/( (√(x−3))×(√(x+3)))) )  =lim_(x→3)  (((√(x−3))/( ((√x)+(√3))×(√(x+3)))) − (1/( (√(x+3)))) )  =−(1/( (√3))) ✓

$${lim}_{{x}\rightarrow\mathrm{3}} \:\left(\frac{\sqrt{{x}}−\sqrt{\mathrm{3}}}{\:\sqrt{{x}−\mathrm{3}}×\sqrt{{x}+\mathrm{3}}}\:−\:\frac{\sqrt{{x}−\mathrm{3}}}{\:\sqrt{{x}−\mathrm{3}}×\sqrt{{x}+\mathrm{3}}}\:\right) \\ $$$$={lim}_{{x}\rightarrow\mathrm{3}} \:\left(\frac{\sqrt{{x}−\mathrm{3}}×\sqrt{{x}−\mathrm{3}}}{\:\left(\sqrt{{x}}+\sqrt{\mathrm{3}}\right)×\sqrt{{x}−\mathrm{3}}×\sqrt{{x}+\mathrm{3}}}\:−\:\frac{\sqrt{{x}−\mathrm{3}}}{\:\sqrt{{x}−\mathrm{3}}×\sqrt{{x}+\mathrm{3}}}\:\right) \\ $$$$={lim}_{{x}\rightarrow\mathrm{3}} \:\left(\frac{\sqrt{{x}−\mathrm{3}}}{\:\left(\sqrt{{x}}+\sqrt{\mathrm{3}}\right)×\sqrt{{x}+\mathrm{3}}}\:−\:\frac{\mathrm{1}}{\:\sqrt{{x}+\mathrm{3}}}\:\right) \\ $$$$=−\frac{\mathrm{1}}{\:\sqrt{\mathrm{3}}}\:\checkmark \\ $$$$ \\ $$

Commented by cortano12 last updated on 18/Jul/23

  = −(1/( (√3) )) (×)    = −(1/( (√6))) (✓)

$$\:\:=\:−\frac{\mathrm{1}}{\:\sqrt{\mathrm{3}}\:}\:\left(×\right) \\ $$$$\:\:=\:−\frac{\mathrm{1}}{\:\sqrt{\mathrm{6}}}\:\left(\checkmark\right) \\ $$

Commented by MM42 last updated on 18/Jul/23

ok  it was my mistake  x→3⇒ −(1/( (√(x+3))))=−(1/( (√6)))

$${ok} \\ $$$${it}\:{was}\:{my}\:{mistake} \\ $$$${x}\rightarrow\mathrm{3}\Rightarrow\:−\frac{\mathrm{1}}{\:\sqrt{{x}+\mathrm{3}}}=−\frac{\mathrm{1}}{\:\sqrt{\mathrm{6}}} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com